Vaginal dysbiosis in women undergoing in vitro fertilisation - D A Khachaturyan; M A Okhrimenko; V Yu Smolnikova; A E Donnikov (IP Berlin A.V., 2013)
The influence of dysbioticvaginal disturbanses on the results of treatment by IVF is stillremainsunclear. Thebacterial vaginosis takes the leading position in the structure of female genital tract infection diseases. Despite of numerous studies which were conducted in this area of investigation, the influence of bacterial vaginosis on treatment in IVF program and ET and also on the subsequent carrying of pregnancy is bad understood till now.